Never Ending Stories: Recent Trends in the Historiography of Jammu and Kashmir - Hewitt, Vernon Marston (History compass, 2007)
This article reviews recent historiography on Jammu and Kashmir, showing how it has sought to escape an overemphasis on independence and partition, and has sought to relocate itself free of the histories of India and Pakistan. In doing so, it has tried to critique the official Indian and Pakistani sources, question the homogeneity of Kashmiri identity, and interrogate the aims and objectives of leading Kashmiri nationalists, primarily that of Sheikh Abdullah. It has also sought to identify the multiplicity of Kashmiri voices premised on issues of culture and language. Energised by the recent violence and turmoil within Indian administered Kashmir, new trends in historiography hold out real potential in offering not just fresh insights but also new and innovative solutions, at some risk of losing sight of the ‘political’ as an subject open to meaningful generalisation and investigation.